Effect of temperature and extraction time on quality of pectin from arabica coffee pulp - Murna Muzaifa; Dian Hasni; Julius Munandar; Ismail Sulaiman; Dedy Rahmad; Rini Ariani Basyamfar (AGROINTEK, 2023)
Coffee is one of the largest commodities in the world. With coffee production more industrialized, waste generated a huge environmental problem. Coffee pulp is the main by-product of coffee processing. One of the components of coffee pulp is pectin. Pectin production from coffee pulp and its characteristics should be studied since extraction conditions used in production vary depending on raw material, desired type of pectin, and process economics. This research aimed to study the characteristics of pectin from coffee pulp extracted using oxalic acid under different times (80 and 90 minutes) and temperatures (100oC and 120oC). The parameters analyzed were yield, equivalent weight, water content, ash content, methoxyl, galacturonic acid, and degree of esterification. The result showed that extraction time and temperature affect the characteristics of pectin. The highest yield was obtained by extraction at 90oC for 90 minutes. The coffee pectin has colored light brown and is categorized as low methoxyl pectin. Overall pectin coffee pulp produced in this study has met the quality requirements of dried pectin by the International Pectin Producer Association (IPPA) standard